Upper airway obstruction in a panfacial fracture - Colombo, Luara Teixeira [UNESP]; Mulinari-Santos, Gabriel [UNESP]; Souza, Francisley Ávila [UNESP] (Wolters Kluwer, 2018)
Panfacial fractures are considered the most aggressive and complex facial fracture, and most of them are the results of a high energy trauma. Therefore, a clinical report of a male patient with a panfacial fracture and Richards type 3 fracture resulting in an airway obstruction is presented. This type of fracture can promote an upper airway obstruction, which needs a correct and fast diagnosis to the life support of the patient.
Keywords: Airway obstruction; Facial trauma; Panfacial fracture